Random walks, boundaries and spectra - Lenz, Daniel; Sobieczky, Florian; Woess, Wolfgang 1954- (Progress in probability, 2011)
These proceedings represent the current state of research on the topics boundary theory and spectral and probability theory of random walks on infinite graphs. They are the result of the two workshops held in Styria (Graz and St. Kathrein am Offenegg, Austria) between June 29th and July 5th, 2009. Many of the participants joined both meetings. Even though the perspectives range from very different fields of mathematics, they all contribute with important results to the same wonderful topic from structure theory, which, by extending a quotation of Laurent Saloff-Coste, could be described by exploration of groups by random processes. Contributors: M. Arnaudon A. Bendikov M. Björklund B. Bobikau D. D?Angeli A. Donno M.J. Dunwoody A. Erschler R. Froese A. Gnedin Y. Guivarch S. Haeseler D. Hasler P.E.T. Jorgensen M. Keller I. Krasovsky P. Müller T. Nagnibeda J. Parkinson E.P.J. Pearse C. Pittet C.R.E. Raja B. Schapira W. Spitzer P. Stollmann A. Thalmaier T.S. Turova R.K. Wojciechows